Implementasi Konsep Teori Humanistik dalam Kesehatan Mental pada Masa Pandemi - Dewi Mahardika; Ulin Nihayah; Hadziq Muhibbuddin (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2021)
Humanistic theory focuses on humans, namely on the nature and condition of humans which includes the ability to understand one's potential and develop it in order to achieve self-actualization. Health is something that is very important in human life. Not only physical or physical health, but also spiritual or mental health. Mental health is a condition in which individuals are healthy both physically and psychologically, aware of their abilities, avoiding mental disorders. Mental health emphasizes how individuals are able to adapt and be able to interact well with the surrounding environment so that they can avoid mental disorders. According to Abraham Maslow, the most important thing in seeing human is their potential, how humans develop themselves to do positive things. Each individual has their own way of dealing with various pressures that can cause mental health problems. Various parts of the world, including Indonesia, are currently facing the COVID-19 pandemic. The current COVID-19 pandemic has caused disruption to human mental health. This writing uses a literature review and the purpose of this paper is to describe the implementation of humanistic theory on mental health during the COVID-19 pandemic. The results of the analysis of research conducted by the author show that common mental health problems during the COVID-19 pandemic are anxiety, stress, depression, and trauma. In humanistic theory, to foster mental health during the COVID-19 pandemic, namely: 1) Every individual is required to try harder in meeting their needs so that they can indirectly control mental health during the pandemic COVID-19. 2) Can conduct therapeutic relationships between counselors and clients to help clients overcome mental health problems experienced.